2018
DOI: 10.1002/elsc.201800095
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid‐enhanced biosynthesis of pharmacologically important lignans and neo lignans in cell suspension culture of Linum ussitatsimum L

Abstract: Linum usitatsimum L. (flax) is a perennial herb with magnitude of medicinal and commercial applications. In the present study, we investigated the effects of salicylic acid (SA) on biosynthesis of lignans (secoisolariciresinol diglucoside (SDG) and lariciresinol diglucoside (LDG)) and neolignans (dehydrodiconiferyl alcohol glucoside (DCG) and guaiacylglycerol‐β‐coniferyl alcohol ether glucoside (GGCG)) in cell cultures of flax. Moderate concentration of SA (50 μM) enhanced biomass accumulation (10.98 g/L dry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
4
19
1
Order By: Relevance
“…No report is present on the production of phenolic compounds in the adventitious root culture of L. usitatissimum until now. However, recently many researchers reported an improvement in the production of phenolics and flavonoids in elicited-cell cultures of L. usitatissimum [13][14][15][16]49], which also endorsed our results. Moreover, many researchers also reported that adventitious root cultures were more potent than callus cultures in the production of phenolic compounds [50].…”
Section: Phenolics Production In Callus and Adventitious Root Culturesupporting
confidence: 90%
See 3 more Smart Citations
“…No report is present on the production of phenolic compounds in the adventitious root culture of L. usitatissimum until now. However, recently many researchers reported an improvement in the production of phenolics and flavonoids in elicited-cell cultures of L. usitatissimum [13][14][15][16]49], which also endorsed our results. Moreover, many researchers also reported that adventitious root cultures were more potent than callus cultures in the production of phenolic compounds [50].…”
Section: Phenolics Production In Callus and Adventitious Root Culturesupporting
confidence: 90%
“…Adventitious roots showed greater antioxidant activity than callus culture, probably due to higher production of phenolics than callus culture. Studies on the antioxidant properties of in vitro cultures of L. usitatissimum are scarce, and only a few reports are available on the antioxidant activity of its callus, hairy root cultures and cell suspension [13][14][15][16]31,32,49]. These investigators reported higher antioxidant activity in hairy root and cell suspension cultures than the callus culture of flax [31].…”
Section: Antioxidant Activity Of Callus and Adventitious Root Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…From that moment, an exponential increase of manuscripts focused on SA (acting alone or in concert with other plant hormones) as a plant growth regulator, signaling molecule, as well as plant elicitor protecting plants from biotic and abiotic stress, was observed [22,23,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%